The efficacy of "walking" bleach technique in endodontically treated teeth: Case report - Savić-Stanković Tatjana; Popović Milica; Karadžić Branislav (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. Discolored teeth in the anterior region can cause considerable cosmetic impairment. One of the techniques commonly used for bleaching endodontically treated teeth is "walking" bleach technique, which in many cases provides satisfying results. The aim of this study was to evaluate bleaching efficacy of "walking" bleach technique in an endodontically treated tooth. Case Report. A 22-year-old patient showed up to the clinic because of discoloration of the maxillary right central incisor. The mixture of sodium perborate and 30% hydrogen peroxide was applied and changed weekly. The total duration of therapy was 28 days. At the end of therapy, the tooth achieved 3 shades lighter color. Conclusion. The mixture of sodium perborate and 30% hydrogen peroxide can successfully bleach discolored endodontically treated teeth.